The impact of renal tubulointerstitial dysfunction on the early and long-term prognosis in chronic heart failure patients with preserved left ventricular ejection fraction - V. V. Syvolap; V. A. Lysenko (Zaporozhye State Medical University, 2024)
Aim. To study the dependence of the early-term (1 year) and long-term (5 years) prognosis in patients with chronic heart failure (CHF) of ischemic origin with preserved left ventricular ejection fraction (LVEF) depending on renal tubulointerstitial functional disorders. Materials and methods. The study involved 88 patients (men - 46.6 % (n = 41); women - 53.4 % (n = 47)) with CHF of ischemic origin, stage II A-B, stage II-IV according to NYHA, 67 % (n = 59) with sinus rhythm, and 33 % (n = 29) with atrial fibrillation. Patients with sinus rhythm and atrial fibrillation were matched in age (p = 0.483), height (p = 0.345), weight (p = 0.317), body surface area (p = 0.153). NGAL levels were analyzed using an ELISA kit (E-EL-H0096, Elabscience, USA). NAG levels were analyzed using an ELISA kit (SEA 069 Hu, Cloud-Clone Corp., USA). KIM-1 levels were analyzed using an ELISA kit (SEA 785 Hu, Cloud-Clone Corp., USA). Kaplan-Meier curves and Cox proportional hazards regression analysis were performed. Results. No significant difference was found in the frequency of the cumulative endpoint during the first-year follow-up from the initial level of two markers of tubulointerstitial injury - KIM-1 (Log-Rank Test: p = 0.57529) and NAG (Log-Rank Test: p = 0.86001). According to the results of analysis of the Cox proportional hazards, only a tendency to increase in the risk factors of adverse events were observed in case of elevated KIM-1 (HR = 1.66; p = 0.5795) and NAG levels (HR = 1.1712; p = 0.8626) in this CHF patients' cohort. Kaplan-Meier analysis revealed a probable (Log-Rank Test; p = 0.00141) increase in the frequency of the cumulative endpoint during the first year of follow-up in CHF patients with preserved LVEF due to increased serum NGAL level more than 168 ng/ml. According to the univariate model, an elevated serum NGAL level is associated with an increase in the relative risk by 4.2 times (95 % CI 1.78-16.89; p = 0.014). A reduced sodium level less than 142.5 mmol/l was associated with an increase in number of adverse cardiovascular events during the first-year follow- ups by 22 % (HR = 1.22, p = 0.029). After 5 years of follow-up, a decrease in sodium level less than 142.3 mmol/l is also characterized by a probable difference of the cumulative Kaplan-Meier's curves (Cox-Mantel F-Test, p = 0.00287). According to the univariate model of Cox proportional hazards, the relative risk of adverse cardiovascular events in patients with CHF during the 5-year follow-up has a tendency to increase by 1.04 times (95 % CI 0.85-1.27; p = 0.72). Serum NGAL, a marker of renal tubulo-interstitial injury, doesn't lose its properties as a powerful marker of an unfavorable long-term prognosis in patients with CHF with preserved LVEF (HR = 5.96; 95 % CI 1.17-30.50; p = 0.032). Conclusions. The most powerful factors of the early (1-year) prognosis of adverse cardiovascular events in CHF patients with preserved left ventricular ejection fraction are the marker of tubulointerstitial injury, serum NGAL over 168 ng/ml, as well as the marker of tubulointerstitial dysfunction - the serum sodium level less than 142.5 mmol/l. The electrolyte imbalance, decreased sodium level less than 142.3 mmol/l, remains a powerful marker of an unfavorable long-term 5-year prognosis in CHF patients with preserved left ventricular ejection fraction, meanwhile serum NGAL, a marker of renal tubulointerstitial injury, besides doesn't lose its prognostic value (HR = 5.96; 95 % CI 1.17-30.50; p = 0.032), but also is independent from the parameters of the age (p = 0.409) and gender (p = 0.397) in such patients.